Terahertz Waveguides: A Bibliometric Analysis of the Past 20 Years - Arslan Ahmed Sohoo; Fauziahanim Che Seman; See Khee yee; Sajjad Ahmed; Izhar Ahmed (Sukkur IBA Journal of Emerging Technologies)
Advancement in technology has opened the doors for the terahertz (THz) frequency range to be applied in different fields for a variety of applications and efficient propagation of THz waves is an important parameter to consider. This paper is a bibliometric analysis of the past twenty years’ research progress toward the terahertz waveguides and their propagation. The analysis is supported by the VOSviewer software. The analysis includes the distribution of the journal publications, contributions by the different authors in the THz waveguide field, affiliations, highly impacted journals, top keywords, and countries working in this area. The analysis discussed in this paper is based on the published reports of the last 20 years extracted from the Scopus database. The main aim of this analysis is to identify the research map, identify the research gap, and the potential of the THz waveguides in future applications. These evaluations would provide a general overview of the development and advancement of the THz waveguide and provide appropriate direction for continuing research in this field